Implementation of Graduate Competency Standards in Quality Control and Development to Improve the Skills of Learners at PKBM Arroyan Pekanbaru - Putri, Melisha Audi; Fahmi, Rahmat (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of Graduate Competency Standards (SKL) in quality control and assurance to improve the skills of learners at PKBM Arroyan Pekanbaru. The study used a qualitative approach with a case study type. Data were obtained through in-depth interviews, observation, and documentation. The results showed that the implementation of SKL was carried out through program planning, implementation of learning based on the learners' needs, and continuous evaluation. This implementation has an impact on improving the skills of learners, especially in aspects of literacy, work skills, and independence. However, there are still obstacles such as limited facilities and heterogeneity of learners. This study concludes that the implementation of SKL in the quality assurance system has an important role in improving the quality of public education